SEMANTIC ANALYSIS AND USE OF AFFIXATIONS IN THE TRANSLATION OF THE SONG SHOLAWAT ATAINAKUM ALBUM AI KHODIJAH: SEMANTIC ANALYSIS AND USE OF AFFIXATIONS IN THE TRANSLATION OF THE SONG SHOLAWAT ATAINAKUM ALBUM AI KHODIJAH - hosniyah, hosniyeh; Mulyati (Jurnal Penelitian Ilmiah INTAJ, 2023)
This research examines the semantics and use of affixations contained in Ai Khodijah's prayer songs. This research was motivated by the large number of fans of prayer songs from various groups, ranging from old people to young people, adults, and even children, especially among Islamic boarding schools, the majority of whom are lovers of prayer songs. And most fans of Sholawat songs still don't understand the use of affixations contained in translations of Sholawat songs, and there are many more affixations contained in them. They also don't know the meaning of the prayer. Meanwhile, the formulation of the problem in this research is: (1) what is the form of semantic analysis and the use of affixation in the translation of the prayer song Atainakum Ai Khodijah?, and (2) what is the meaning of the word forms that undergo the affixation process in the translation of the prayer song Atainakum Ai Khodijah? Meanwhile, the method used in this research is descriptive-qualitative, and the approach used is a qualitative approach. In this study, researchers found 11 words that used affixations, 8 explicit meanings were found, and 11 words had implied meanings.